Alteration in Oral Microbiome Among Men Who Have Sex With Men With Acute and Chronic HIV Infection on Antiretroviral Therapy - Li, Shuang; Zhu, Junping; Su, Bin; Wei, Huanhuan; Chen, Fei; Liu, Hongshan; Wei, Jiaqi; Yang, Xiaodong; Zhang, Qiuyue; Xia, Wei; Wu, Hao; He, Qiushui; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Despite the antiretroviral therapy (ART), human immunodeficiency virus (HIV)-related oral disease remains a common problem for people living with HIV (PLWH). Evidence suggests that impairment of immune function in HIV infection might lead to the conversion of commensal bacteria to microorganisms with increased pathogenicity. However, limited information is available about alteration in oral microbiome in PLWH on ART. We performed a longitudinal comparative study on men who have sex with men (MSM) with acute HIV infection (n=15), MSM with chronic HIV infection (n=15), and HIV-uninfected MSM controls (n=15). Throat swabs were collected when these subjects were recruited (W0) and 12 weeks after ART treatment (W12) from the patients. Genomic DNAs were extracted and 16S rRNA gene sequencing was performed. Microbiome diversity was significantly decreased in patients with acute and chronic HIV infections compared with those in controls at the sampling time of W0 and the significant difference remained at W12. An increased abundance of unidentified Prevotellaceae was found in patients with acute and chronic HIV infections. Moreover, increased abundances of Prevotella in subjects with acute HIV infection and Streptococcus in subjects with chronic HIV infection were observed. In contrast, greater abundance in Lactobacillus, Rothia, Lautropia, and Bacteroides was found in controls. After effective ART, Bradyrhizobium was enriched in both acute and chronic HIV infections, whereas in controls, Lactobacillus, Rothia, Clostridia, Actinobacteria, and Ruminococcaceae were enriched. In addition, we found that lower CD4+ T-cell counts (<200 cells/mm3) were associated with lower relative abundances of Haemophilus, Actinomyces, unidentified Ruminococcaceae, and Rothia. This study has shown alteration in oral microbiome resulting from HIV infection and ART. The results obtained warrant further studies in a large number of subjects with different ethnics. It might contribute to improved oral health in HIV-infected individuals.